The Impact of Parental Psychiatric Symptoms and Parent-Child Relationships on Behavioural and Emotional Problems in Newly-Diagnosed Toddlers and Preschool Children with Autism Spectrum Disorders - Bilgiç, Ayhan; Uzun, Necati (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Background: Emotional and behavioural problems occur at a high rate in children with autism spectrum disorders (ASD). These problems are associated with a broad range of risk factors such as parental psychopathology and family environment in school-age children and adolescents. However, limited information is available about these phenomena in toddlers and preschool children. This cross-sectional study examined the association of maternal and paternal psychiatric symptoms and mother-child relationships with emotional and behavioural problems and socioemotional competence of newly-diagnosed young children with ASD. Method: Autistic symptoms, developmental level, and mother-child relationship of children were evaluated. Parents completed a checklist on child behavioural and emotional problems, and individual questionnaires on their own mental health. Results: Participants were 35 children with ASD aged 18 – 53 months, referred to an infant mental health clinic. Maternal hostility and poor mother-child relationships have been found to be independently associated with emotional and behaviour problems in these children. Conclusions: This study suggests that maternal hostility and mother-child relationship problems may play a role for the development of emotional and behaviour problems in toddlers and preschool children with ASD.